PENGEMBANGAN MODEL MANAJEMEN PEMASARAN DIGITAL UNTUK UMKM KABUPATEN SIMALUNGU - Uning Heri Gagarin; Obet Hendra Berutu; Hendri Mayanta (Yayasan Nusantara Hasana Berdikari, 2024)
This community service program (PkM) aims to develop and implement a practical digital marketing management model for urban MSMEs to enhance visibility, customer engagement, and sales through digital channels. The partners’ challenges include inconsistent content, weak brand identity, unoptimized use of marketplaces and social media, and the absence of marketing performance indicators (KPIs). The methods applied include assessing MSMEs’ digital readiness, developing the model (segmentation–positioning, funnel, content calendar, response SOPs, ad management, and KPI dashboard), conducting training and mentoring clinics, piloting campaigns over a specified period, and performing data-driven evaluations. The outputs consist of a digital marketing model package and practical tools that can be replicated by other MSMEs.